Quasi-experimental evidence on the effectiveness of heart attack treatment in Germany - Corinna Hentschker; Ansgar Wuebker (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2018)
Objective. To examine the causal effect of percutaneous transluminal coronary angioplasty (PTCA) in comparison to conservative treatment methods on mortality. Data Sources. We use a full sample of administrative hospital data from Germany for the years 2005 to 2007. Study Design. To account for non-random treatment assignment of PTCA, instrumental variable approaches are implemented that aim to randomize patients into getting PTCA independent of heart attack severity. Instruments include differential distances to PTCA hospitals and regional PTCA rates. Principal Findings. Our results suggest a 4.5 percentage point mortality reduction for patients who have access to PTCA compared to patients receiving only conservative treatment. We relate mortality reduction to the additional costs for this treatment and conclude that PTCA treatment is cost-effective in lowering mortality for AMI patients at reasonable cost-effectiveness thresholds. Conclusions. Our local average treatment effect results suggest that PTCA treatment could be beneficial, at least for the group that did not receive PTCA because the nearest hospital did not provide PTCA.
Keywords: 330; Acute myocardial infarction; instrumental variables; mortality